1993
DOI: 10.7556/jaoa.1993.93.12.1273
|View full text |Cite
|
Sign up to set email alerts
|

Myofascial manipulative release of carpal tunnel syndrome: Documentation with magnetic resonance imaging

Abstract: Four patients with carpal tunnel syndrome, unresponsive to routine conservative care, underwent treatment with myofascial release manipulation and selfstretching. Magnetic resonance imaging analysis of the cross-sectional area of the carpal tunnel and electrodiagnosis were performed before and after treatment. The patients improved clinically. The nerve conduction studies showed concomitant reduction in distal latencies or increase in motor response amplitudes. Magnetic resonance imaging demonstrated that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 2 publications
3
28
0
Order By: Relevance
“…It represents a widely employed manual technique specific for fascial tissues, to reduce adhesions, restore and/or optimise fascia sliding mobility in both acute and chronic conditions (Barnes, 1996;Martin, 2009;Sucher, 1993;Walton, 2008). Some studies have shown the efficacy of MFR to decrease pain, improve posture, and quality of life (Barnes, 1990;Fernandez de las Penas et al, 2005;LeBauer et al, 2008;Lukban, 2001;Radjieski et al, 1998).…”
Section: Introduction Fascia and Mftsmentioning
confidence: 94%
“…It represents a widely employed manual technique specific for fascial tissues, to reduce adhesions, restore and/or optimise fascia sliding mobility in both acute and chronic conditions (Barnes, 1996;Martin, 2009;Sucher, 1993;Walton, 2008). Some studies have shown the efficacy of MFR to decrease pain, improve posture, and quality of life (Barnes, 1990;Fernandez de las Penas et al, 2005;LeBauer et al, 2008;Lukban, 2001;Radjieski et al, 1998).…”
Section: Introduction Fascia and Mftsmentioning
confidence: 94%
“…Few studies have examined the effectiveness of myofascial release (MFR) techniques on the direct parameters of patient outcomes (Hanten, 1994;Barnes, 1997;Bucher, 1993Bucher, , 1994Weiselfish-Giammatteo and Kain, 2005). Additionally, experimental research does not exist that compares the effectiveness of MFR outcomes versus any modality intervention.…”
Section: Introductionmentioning
confidence: 98%
“…Manipulating carpal tunnel mechanics without transecting the TCL, by either myofascial release [8] or using a wearable hand traction device [9], has shown to improve the symptoms of carpal tunnel syndrome. Reconstruction of the TCL after carpal tunnel release has been shown to restore the gliding and pulley mechanisms of the flexor tendons and to improve hand function [6].…”
Section: Introductionmentioning
confidence: 99%